Use of antidementia drugs in German patients with Alzheimer's disease. (March 2018) - Hessmann, Philipp; Dodel, Richard; Baum, Erika; Müller, Matthias J.; Paschke, Greta; Kis, Bernhard; Zeidler, Jan; Klora, Mike; Reese, Jens-Peter; Balzer-Geldsetzer, Monika
Abstract : The objective of this study was to evaluate the use of antidementia drugs (ADDs) in patients with Alzheimer's disease (AD) regarding German guideline recommendations and to assess correlations between the use of ADDs and the patients' characteristics. A total of 395 community-dwelling and institutionalized patients with AD across all severity stages of dementia were recruited in this cross-sectional study. Associations between the prescription of ADDs and patients' sociodemographic and clinical parameters (neuropsychiatric symptoms, cognitive capacity, daily activities, and health-related quality of life) were analyzed in multiple logistic regression analyses. ADDs were prescribed in 46.6% of all participants and less often in institutionalized patients (38.2 vs. 50.4%, P =0.025). Patients with mild-to-moderate dementia had a higher chance of receiving ADDs [odds ratio (OR)=3.752, 95% confidence interval (CI): 1.166–12.080 and OR=3.526, 95% CI: 1.431–8.688] as well as those treated by neurologists/psychiatrists (OR=2.467, 95% CI: 1.288–4.726). Overall, 39% of the patients with mild cognitive deficits (Mini-Mental Status Examination 27–30) received ADDs and 21% of the mildly demented patients (Mini-Mental Status Examination 20–26) received memantine. The treatment with ADDs was in part not in line with German guideline recommendations. Particularly, the lower use of ADDs in patients not attending neuropsychiatric specialists should be further evaluated.